Authority versus Persuasion - Van den Steen, Eric (American Economic Review, 2009)
Managers often face a choice between authority and persuasion. In particular, since a firm’s formal and relational contracts and its culture and norms are quite rigid in the short term, a manager who needs to prevent an employee from undertaking the wrong action has the choice between either trying to persuade this employee or relying on interpersonal authority. 1 Simon (1947) noted, for example, that ‘when... disagreement is not resolved by discussion, persuasion, or other means of conviction, then it must be decided by the authority of one or the other participant ’ and that ‘in actual practice [...] authority is liberally admixed with suggestion and persuasion. ’ Obviously, in choosing between persuasion and authority the manager makes a cost-benefit trade-off. This paper studies that trade-off, focusing in particular on agency conflicts that originate in open disagreement, in the sense of differing priors. To that purpose, I will study a setting in which a principal and an agent are involved in a project. The project’s outcome depends on decisions by both the principal and the agent and also depends on complementary private effort by the agent. A key issue is that the principal and agent may openly disagree on which decisions are most likely to lead to a success, even though no player has private information, i.e. the players have differing